2023
DOI: 10.1111/tid.14141
|View full text |Cite
|
Sign up to set email alerts
|

Trough ganciclovir concentration as predictor of leukopenia in lung transplant recipients receiving valganciclovir prophylaxis

Yoshiki Katada,
Shunsaku Nakagawa,
Miki Nagao
et al.

Abstract: BackgroundValganciclovir is the first‐line agent for Cytomegalovirus prophylaxis after lung transplantation. However, its use is associated with a relatively high risk of hematological toxicity. This study aimed to investigate the relationship between trough ganciclovir concentration and hematologic toxicity in lung transplantation patients receiving valganciclovir prophylaxis, and identify factors that affect ganciclovir pharmacokinetics in this population.MethodsThis prospective observational study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this case, the initial valganciclovir dosage was established considering renal function; nevertheless, the patient encountered a decline in the white blood cell count to 2,220/μL. The results of our previous study suggested that a ganciclovir trough concentration of 872 ng/ mL or higher is associated with severe leukopenia [9]. We adjusted the valganciclovir dosage based on the trough serum concentrations of ganciclovir and successfully administered it without CMV reactivation or significant adverse effects.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In this case, the initial valganciclovir dosage was established considering renal function; nevertheless, the patient encountered a decline in the white blood cell count to 2,220/μL. The results of our previous study suggested that a ganciclovir trough concentration of 872 ng/ mL or higher is associated with severe leukopenia [9]. We adjusted the valganciclovir dosage based on the trough serum concentrations of ganciclovir and successfully administered it without CMV reactivation or significant adverse effects.…”
Section: Discussionmentioning
confidence: 95%
“…The patient experienced continuous post-hemodiafiltration withdrawal and exhibited relatively impaired renal function, leading us to hypothesize that this condition might delay ganciclovir excretion and heighten the risk of severe leukopenia. To avoid cessation of valganciclovir prophylaxis, we performed TDM to maintain trough concentrations of ganciclovir below 872 ng/mL, which is less toxic than that previously reported by our group [9]. Serum ganciclovir concentrations were measured using liquid chromatography-tandem mass spectrometry as described previously [9].…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations